Inflammation in uveal melanoma - Bronkhorst, I H G (Nature Publishing Group, 2013)
Leukocytic infiltration is a common feature of human cancers, including those that develop in immunoprivileged sites, such as the eye. The infiltration of myeloid and T cells into tumours is part of the host response against cancer. In uveal melanoma, high densities of immune cells seem to be involved in tumour progression, as they are associated with the loss of one chromosome 3. The nature of this tumour microenvironment might offer therapeutic opportunities.